(untitled) (Forum Agribisnis, 2026)
Indonesia’s cocoa industry still faces various challenges in enhancing its competitiveness in the international market, as evidenced by the dominance of raw material exports and fluctuations in export performance. In light of these conditions, the government has implemented an export tax policy on cocoa beans as an effort to promote downstream processing and increase value added. This study aims to analyze the development of Indonesia’s cocoa exports following the implementation of this policy and to assess its impact on the competitiveness of Indonesian cocoa in the global market. The method used in this study is a quantitative descriptive approach utilizing secondary data from the 2020–2024 period. Competitiveness was measured using the Revealed Comparative Advantage (RCA) indicator, while export performance was analyzed through changes in export volume and value. The results indicate that the export tax policy has driven a shift in the structure of Indonesia’s cocoa exports, characterized by a decline in raw cocoa bean exports and an increase in the contribution of processed products. Although export volumes fluctuated, export values remained relatively stable and tended to increase, reflecting a shift toward commodities with higher value added. Furthermore, RCA values above one during most of the period indicate that Indonesia still possesses a comparative advantage in the international market. These findings suggest that export tax policies indirectly influence competitiveness by strengthening the downstream sector. The policy implications of this research are the need to enhance the capacity of the processing industry, improve productivity and cocoa quality at the upstream level, and maintain a balance between the interests of farmers and the industry so that downstreaming policies can promote sustainable competitiveness.